Would you have your future children vaccinated? a study among foundation program students in a Malaysian public university - Ahmad, Norliza; Lim, Poh Ying; Ganesen, Disalini; Nor Hazalan, Marsha Hedaya; Ng, Jyi Cheng (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: There are a growing number of parents who hesitate to vaccinate their children. Therefore, the current study was conducted to assess future parents-to-be intention to vaccinate their children, as well as to investigate con- tributing factors of vaccination intention and to identify sources of information on childhood vaccination. Method: A cross-sectional study was conducted among Foundation Program students at a public university for five months, from April to August 2019. Factors studied included sociodemographic characteristics, knowledge and attitudes to- ward childhood immunization, and religiosity. Data were collected using a validated self-completed questionnaire. Simple random sampling was conducted, with a total of 371 students were recruited as respondents. Multiple logistic regression was performed to determine the predictors. The significance level is set at alpha less than 5%. Results: Approximately 95% of respondents indicated an intention to vaccinate their future. The mean age of respondents was 19 ± 0.37 years old. A motive to vaccinate their future children was high among females (AOR: 4.20, 95% CI: 1.59, 11.08, p: 0.004), having sufficient knowledge about childhood vaccination (AOR: 3.92, 95% CI: 1.23, 12.45, p: 0.021), and having a positive attitude toward childhood vaccination (AOR: 9.56, 95% CI: 2.15, 42.46, p: 0.003). There was no significant association between intention to have their future children vaccinated and religiosity. The sources of information about childhood vaccination were mainly the Internet (72%), mass media (68.2%), and social media (61.7%). Conclusion: Readiness of foundation program students was satisfactory. However, policymakers and program planners should target improving knowledge and attitudes of young people about childhood immunization especially among young men as they will head the household. This effort may sustain the readiness of young people to vaccinate their future children. The approach should include the Internet, mass media, and social media.